Efektifitas Penggunaan Media Video pada Pembelajaran Tematik Terpadu di Sekolah Dasar Saat Pandemi Covid-19 - Ridha, Mhd.; Firman, Firman; Desyandri, Desyandri (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
Learning media is an important factor in learning activities. Media becomes an intermediary between educators and students in delivering learning material.The outbreak of the Covid-19 pandemic in Indonesia has had a significant impact on Indonesian education. Educational activities carried out online from home. One of the learning media that is an alternative for educators during the Covid-19 pandemic is the use of video media. The purpose of this study was to see the extent to which video media was implemented in elementary schools during the Covid-19 pandemic based on the perspective of educators. The methodology used in this research is quantitative descriptive with an instrument in the form of a questionnaire distributed to elementary school educators in West Sumatra in December 2020. The results show that the implementation of learning during the Covid-19 pandemic using video learning media in elementary schools has been running smoothly. good. Learning video media was effectively implemented during the Covid-19 pandemic, because it made it easier for educators to teach material and made it easier for students to understand learning material.